Unlocking the potential: A comprehensive review on blast furnace slag and silica analog adsorbents for sustainable industrial and pharmaceutical pollution control and resource utilization - Qing-Guo Dong; Jing Li; Zhi-Qing Kang; Muhammad Imran Anwar; Muhammad Asad; Baoji Miao; Shuanghu Wang; Ayesha Younas (Emerging Contaminants)
Blast furnace slag (BFS) is a secondary material generated during the process of producing iron in blast furnaces, prompting scholars to concentrate on its efficient management and broad application for the creation of valuable commodities. This study examines the mineral composition, adsorption characteristics, and utilization of BFS and its silica counterparts. Recent developments in the application of BFS and its functionalized materials for pollution mitigation are examined, specifically concentrating on the elimination of nitrogen, phosphorus, metal ions, pharmaceutical effluents, waste oils, and dye molecules from wastewater. Moreover, these inexpensive adsorbents exhibit significant specific surface areas, possess microporous configurations, and contain alkaline components like calcium oxide, magnesium oxide, and aluminum oxide. This review further elucidates the present state of BFS-based adsorbents in the absorption of acid gases, with a specific focus on CO₂. The problems associated with widespread BFS usage are analyzed, and potential solutions for effective resource utilization are discussed.